John Adolphus Bernard Dahlgren papers - Dahlgren, John Adolphus Bernard, 1809-1870.
Correspondence, letterbooks, journals, reports, logbooks, orders, notes, notebooks, nautical calculations and charts, scrapbooks, and design drawings relating to Dahlgren's activities in the development of ordnance for the U.S. Navy and as Chief of the Bureau of Ordnance. Includes journals of cruises as midshipman, and logbooks kept during his Civil War service in the South Atlantic. Correspondents include his son Ulric Dahlgren, Samuel Francis Du Pont, Andrew Hull Foote, Gustavus Fox, and Gideon Welles.
Naval officer, inventor, and author.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Dahlgren, Ulric, -- 1842-1864 -- Correspondence; Du Pont, Samuel Francis, -- 1803-1865 -- Correspondence; Foote, Andrew H. -- 1806-1863 -- Correspondence; Fox, Gustavus Vasa, -- 1821-1883 -- Correspondence; Welles, Gideon, -- 1802-1878 -- Correspondence; United States. -- Navy -- History -- Civil War, 1861-1865.; United States. -- Navy -- Ordnance and ordnance stores; United States. -- Navy Department. -- Bureau of Ordnance; Ordnance -- Design and construction; United States -- History -- Civil War, 1861-1865 -- Naval operations; Authors; Inventors; Naval officers